2021
DOI: 10.1093/tas/txab204
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal in situ degradability of forage components and in vitro organic matter digestibility of warm-season grasses treated with calcium oxide

Abstract: An experiment was designed to evaluate the effects of CaO on ruminal in situ degradability (RISD) of forage components and in vitro organic matter digestibility (IVOMD) of warm-season forages. Bahiagrass (Paspalum notatum; BH) or Tifton 85 bermudagrass (Cynodon spp.; BM) hay were stored in 20-L buckets in two consecutive years (n = 4/treatment) as follows: 1) untreated dry BH or BM (DH); 2) hydrated BH or BM stored for 7 d (W7); 3) hydrated BH or BM stored for 14 d (W14); 4) hydrated BH or BM + 5% [dry matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The researchers reported that the optimum concentration of rumen NH 3 -N should be 5 to 27.5 mg/dL (Huhtanen et al, 2015;Karimizadeh et al, 2017;Antunes et al, 2019;Gruninger et al, 2019;Ciriaco et al, 2021). The highest concentration of NH 3 -N in this trial was in the 80:20 group at 31.00 mg/dL, which also had the highest protein content.…”
Section: Effects Of Different Diets On Ammonia-nitrogen Concentration...mentioning
confidence: 68%
“…The researchers reported that the optimum concentration of rumen NH 3 -N should be 5 to 27.5 mg/dL (Huhtanen et al, 2015;Karimizadeh et al, 2017;Antunes et al, 2019;Gruninger et al, 2019;Ciriaco et al, 2021). The highest concentration of NH 3 -N in this trial was in the 80:20 group at 31.00 mg/dL, which also had the highest protein content.…”
Section: Effects Of Different Diets On Ammonia-nitrogen Concentration...mentioning
confidence: 68%
“…A modified Tilley and Terry 48 procedure was used to determine the in vitro organic matter digestibility. Preparations of samples and assay steps were followed according to Ciriaco et al 49 . Four consecutive incubation runs were carried out with three flasks per substrate in addition to three blanks (no substrate).…”
Section: Methodsmentioning
confidence: 99%